A cosmological controversy in the renaissance: Marsilioficino’s and giovanni pico della mirandola’s contrasting views on the animation of the heavens - Rutkin, H. Darrel (2021)
In the early twenty-first century, we often ask whether there is life (intelligent or other-wise) in the cosmos, but almost never whether the heavens themselves are actually alive or animated, that is, infused somehow with a soul, the anima mundi, or some such entity. This was not the case in the Middle Ages, the Renaissance, or the early modern period. Although Aristotelians normally answered no to this question, Marsilio Ficino (1433–99) took a decidedly Platonic turn when he answered the question positively, insistently, and consistently in a broad range of works over his entire philosophical career. By contrast, Giovanni Pico della Mirandola (1463–94), Ficino’s younger contemporary, began by embracing the new Platonic position but joined the Aristotelian fold in his later works. In this essay, I will briefly compare and contrast Ficino’s solid and consistent position with the changing trajectory of Pico’s views over the course of his short but intense career. This essay is an exploration of central themes and some preliminary reflections thereon. These essentially Platonic views of a living universe provide the conceptual and literary foundations for understanding this issue in the early modern period.
Created from Fastlane, Scopus look-up

Astrology and Magic - Rutkin, H Darrel (A Companion to Albert the Great, 2013)

Astrology - from Part III - Dividing the Study of Nature - Rutkin, H. Darrel (The Cambridge History of Science, 2006)
As is well known, astrology finally disappeared from the domain of legitimate natural knowledge during the seventeenth and eighteenth centuries, although the precise contours of this story remain obscure. It is less well known, albeit clearly documented, that astrology was taught from the beginning of the fourteenth century as an important part of the arts and science curriculum at the great medieval and Renaissance universities, including Padua, Bologna, and Paris. There, astrology was studied within three distinct scientific disciplines – mathematics, natural philosophy, and medicine – and served to integrate several highly developed mathematical sciences of antiquity – astronomy, geography, and geometrical optics – with Aristotelian natural philosophy. This astrologizing Aristotelianism provided fundamental patterns of interpretation and analysis in pre-Newtonian natural knowledge. Thus, the history of astrology – and, in particular, the story of its protracted criticism and ultimate rejection as a source of what the learned considered legitimate natural knowledge – is central for understanding the transition from medieval and Renaissance natural philosophy to Enlightenment science. The role of astrology in this transition was neither obvious nor unproblematic. Indeed, astrology’s integration of astronomy and natural philosophy under the aegis of mathematics had much in common with the aims of the “new science” of the seventeenth century. Thus it becomes necessary to explain why this promising astrological synthesis was rejected in favor of a rather different mathematical natural philosophy.<br

Astrology, Politics and Power in 16th-century Florence: Giuliano Ristori’s Extensive Judgment on Cosimo I’s Nativity (1537) - Rutkin, H Darrel (Astrologers and their Clients in Medieval and Early Modern Europe, 2013)

How to Accurately Account for Astrology's Marginalization in the History of Science and Culture: The Essential Importance of an Interpretive Framework - Rutkin, H Darrel (Early Science and Medicine, 2018)

Is Astrology a Type of Divination? Thomas Aquinas, the Index of Prohibited Books, and the Construction of a Legitimate Astrology in the Middle Ages and the Renaissance - Rutkin, H. Darrel (International Journal of Divination and Prognostication, 2019)
What is the relationship between astrology and divination? In particular, is astrology a type of divination, as is often asserted or assumed? In both astrology and divination, knowledge and prediction of the future are primary goals, but does this warrant calling astrology a form of divination? I approach these questions by exploring the response of Thomas Aquinas, which was to be extremely influential for many centuries. First I analyze in some detail Thomas’s answer in his Summa theologiae 2-2.92–95; then I discuss two significant sixteenth-century examples of its influence: the 1557, 1559, 1564, and later indexes of prohibited books; and Pope Sixtus V’s anti-divinatory bull, Coeli et Terrae Creator (1586). In this way, we can explore some of the complex historical dynamics at play in the construction of a legitimate astrology in the Middle Ages and the Renaissance.<br
Keywords: History of science; history of astrology; Middle Ages; Renaissance; Thomas Aquinas; legitimate knowledge; divination; Index of Prohibited Books

Optimus Malorum: Giovanni Pico della Mirandola’s Complex and Highly Interested Use of Ptolemy in the Disputationes adversus astrologiam divinatricem (1496), A Preliminary Survey - Rutkin, H. Darrel (Ptolemy’s Science of the Stars in the Middle Ages, 2020)

Sapientia Astrologica: Astrology, Magic and Natural Knowledge, ca. 1250-1800 - Rutkin, H. Darrel (Springer, 2019)
This book explores the changing perspective of astrology from the Middle Ages to the Early Modern Era. It introduces a framework for understanding both its former centrality and its later removal from legitimate knowledge and practice. The discussion reconstructs the changing roles of astrology in Western science, theology, and culture from 1250 to 1500. The author considers both the how and the why. He analyzes and integrates a broad range of sources. This analysis shows that the history of astrology—in particular, the story of the protracted criticism and ultimate removal of astrology from the realm of legitimate knowledge and practice—is crucial for fully understanding the transition from premodern Aristotelian-Ptolemaic natural philosophy to modern Newtonian science. This removal, the author argues, was neither obvious nor unproblematic. Astrology was not some sort of magical nebulous hodge-podge of beliefs. Rather, astrology emerged in the 13th century as a richly mathematical system that served to integrate astronomy and natural philosophy, precisely the aim of the “New Science” of the 17th century. As such, it becomes a fundamentally important historical question to determine why this promising astrological synthesis was rejected in favor of a rather different mathematical natural philosophy—and one with a very different causal structure than Aristotle'
Keywords: Astrology and the history of science; Astrology and medieval science; Astrology and magic (talismans); Astrology and medieval philosophy; Astrology and the Scientific Revolution; Astrologizing Aristotelianism; Aristotelian Natural Philosophy; Albertus Magnus; Speculum astronomiae; Roger Bacon; Thomas Aquinas; Mathematics and Humanism; mathematical system; Aristotelian-Ptolemaic; Annus Mirabilis of 1484; Revolutions Intermezzo; Opera et verba sapientiae

The Use and Abuse of Ptolemy’s Tetrabiblos in Renaissance and Early Modern Europe: Two Case Studies (Giovanni Pico della Mirandola and Filippo Fantoni) - Rutkin, H. Darrel (Ptolemy in Perspective, 2010)
Not so very long ago, astrology was taught within the scientific curriculum of the finest European universities, especially in Italy, where it was taught from at least the beginning of the fourteenth through the middle of the seventeenth centuries. According to the University of Bologna’s 1405 statutes, which articulate the basic structures of arts education in the premodern Italian universities, astrology was primarily taught in the four-year mathematics course, although it was also taught in different respects in the natural philosophy and medical courses. After prerequisites in arithmetic, geometry and elementary mathematical astronomy, the students began their study of astrology proper in the third year; in the fourth, they advanced to the higher levels of scientific astronomy and astrology by reading two of Ptolemy’s fundamental texts, the Almagest and Tetrabiblos.1
Created from Fastlane, Scopus look-up
Keywords: Celestial Body; Disciplinary Structure; Heavenly Body; Latin Translation; Seventeenth Century

Various Uses of Horoscopes: Astrological Practices in Early Modern Europe - Rutkin, H Darrel (Horoscopes and Public Spheres, 2013)